FORAGE PRODUCTION OF SOME LESSER-KNOWN LEUCAENA SPECIES GROWN ON ACID SOIL - Purwantari, Nurhayati D. (Indonesian Agency for Agricultural Research and Development - MOA, 2005)
Leucaena leucocephala leaves are nutritious and palatable for ruminants. However, the plant is poorly adapted on acid soil, water logged, and susceptible to psyllid (Heteropsylla cubana). Leucaena favours soils with pH >5. It performs best on calcareous soils. This study aimed to evaluate adaptability of several Leucaena species on acid soils. The study was conducted at the experimental field in Ciawi, Bogor, altitude 500 m abovesea level, rainfall 1500-2000 mm year-1, on Latosol soil with pH 5.2. Leucaena species evaluated were L. leucocephala K28, L. leucocephala (local type), Leucaena KX2 hybrid, L. collinsii, L. trichandra, and L. diversifolia. Experiment was designed in a randomized complete block, four replications. All the seedlings were grown in the nursery for 2.5 months before being transplanted to the field. The plants were grown in row plots of 5 m x 1 m with planting distance 0.5 m and spacing between row plot was 3 m. One unit replicate was 5 m x 21 m. In wet season, the plants were pruned at 50 cm height every 3 months, whilst in dry season pruning was done every 5 months. Parameter measured were plant regrowth and forage production (edible part and non-edible part of the plant), as well as N and P content of the edible part. The result showed that Leucaena KX2 hybrid was superior to other leucaenas. Regrowthof KX2 hybrid was the fastest and produced highest forage. The highest fresh weight forage production for 1 year (four times harvests), i.e. 33.93 t ha-1 year-1 equal to 12.48 t ha- 1 year-1 of dry weight, was obtainedÂ from Leucaena KX2 hybrid, whereas the lowest was produced by L.Â diversifolia, i.e. 3.12 t ha-1 year-1 of fresh weight or 1.01 t ha-1 year-1 of dry weight. Production of non-edible part followed the pattern of production of edible part. N and P content in the edible part of all Leucaena species did not show any significant difference except for L. trichandra which contained the lowest. This study implies that Leucaena KX2 hybrid is adaptable to acid soil; therefore it can be grown in wider areas throughout Indonesia.